Pengaruh Model Pembelajaran Inkuiri dan Kemampuan Komunikasi Matematis terhadap Hasil Belajar Siswa - Faruq Faruq; Rudy Sumiharsono; Eges Triwahyuni (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
The research objectives were: to find out 1) is there an effect of the inquiry learning model on learning outcomes, 2) is there an effect of mathematical communication skills on learning outcomes, and 3) is there an influence of the inquiry learning model and mathematical communication skills together on the learning outcomes of Class VIII students -A and VIII-B at MTs Negeri 5 Banyuwangi. The research design is causal quantitative. The method of determining the area by purposive sampling area. The population research technique population research as many as 42 students. Data collection techniques: 1). interview, 2). observation, 3). documentation, 4). questionnaire, 5). test. Questionnaire data was tested through instrument testing, validity testing and reliability testing. The classic assumption test includes the normality test, homogeneity test, autocorrelation test, heteroscedasticity test, and finally the hypothesis test includes the t test and F test. The results of the t test, the effect of the inquiry learning model on learning outcomes t count is higher than t table (1.446> 0.681). The results of the t test, the effect of mathematical communication skills on learning outcomes t count higher than t table (6.454> 0.681), F test results, the effect of inquiry learning models and mathematical communication skills on learning outcomes F count value is greater than F table (3.427 >3,24).